Sustained release of hepatocyte growth factor by cationic self-assembling peptide/heparin hybrid hydrogel improves β-cell survival and function through modulating inflammatory response - Liu S (Dove Medical Press, 2016)
Shuyun Liu,1 Lanlan Zhang,2 Jingqiu Cheng,1 Yanrong Lu,1 Jingping Liu1 1Key Laboratory of Transplant Engineering and Immunology, West China Hospital, 2Institute for Nanobiomedical Technology and Membrane Biology, Sichuan University, Chengdu, People’s Republic of China Abstract: Inflammatory response is a major cause of grafts dysfunction in islet transplantation. Hepatocyte growth factor (HGF) had shown anti-inflammatory activity in multiple diseases. In this study, we aim to deliver HGF by self-assembling peptide/heparin (SAP/Hep) hybrid gel to protect β-cell from inflammatory injury. The morphological and slow release properties of SAPs were analyzed. Rat INS-1 β-cell line was treated with tumor necrosis factor α in vitro and transplanted into rat kidney capsule in vivo, and the viability, apoptosis, function, and inflammation of β-cells were evaluated. Cationic KLD1R and KLD2R self-assembled to nanofiber hydrogel, which showed higher binding affinity for Hep and HGF because of electrostatic interaction. Slow release of HGF from cationic SAP/Hep gel is a two-step mechanism involving binding affinity with Hep and molecular diffusion. In vitro and in vivo results showed that HGF-loaded KLD2R/Hep gel promoted β-cell survival and insulin secretion, and inhibited cell apoptosis, cytokine release, T-cell infiltration, and activation of NFκB/p38 MAPK pathways in β-cells. This study suggested that SAP/Hep gel is a promising carrier for local delivery of bioactive proteins in islet transplantation. Keywords: self-assembling peptide, islet transplantation, inflammation, HGF, slow release